Diagnostic metabolite biomarkers of chronic typhoid carriage - Näsström, Elin; Jonsson, Pär; Johansson, Anders; Dongol, Sabina; Karkey, Abhilasha; Basnyat, Buddha; Tran Vu Thieu, Nga; Trinh Van, Tan; Thwaites, Guy E.; Antti, Henrik; Baker, Stephen (PLOS Neglected Tropical Diseases, 2018)
Author summary Enteric fever, caused by typhoidal Salmonella serovars, remains a substantial public health problem in many low- and middle-income countries. The human-restricted nature of these organisms combined with the development of new vaccines suggests that regional elimination of enteric fever should be possible. However, individuals that chronically carry Salmonella in their gallbladder, such as the notorious Typhoid Mary, complicates enteric fever transmission and maintain circulation of the organisms. The prospective detection of chronic Salmonella carriers is therefore a critical step for regional enteric fever elimination. However, there are currently no diagnostic methods routinely in use for this purpose. Here, we used a novel method for identifying chronic Salmonella carriers by comparing metabolite patterns in plasma samples from patients with chronic Salmonella carriage against non-carriage controls. We could significantly distinguish Salmonella carriers from non-carriers based on a large set of metabolites. Five metabolites were then highlighted, after comparing metabolite patterns obtained during chronic Salmonella carriage and acute enteric fever respectively, which could significantly distinguish Salmonella carriers from non-carriers. These potential biomarkers require further evaluation in epidemiological investigations of enteric fever in alternative endemic settings but this study provides a first step towards improved detection of Salmonella carriers.